Improvement of Selectivity and Antifouling Properties of Chitosan-modified Polyvinylidene Fluoride (PVDF) Membrane for Protein Filtration - Reza Zatadini; Aldita Fatchul Ni’mah; Yudi Setiawan; Agung Lucky Pradita; Desy Vita Pratiwi; Dina Syakirina; Mayzy Vanesia Insani; Widyan Muhammad Naufal; Wulida Rayhani; Edi Pramono; Ozi Adi Saputra (UNIVERSITAS SEBELAS MARET (UNS), 2023)
Protein with high purity is currently a valuable commercial commodity, prized for its high value and application in specialized functions. PVDF-based membrane technology has found widespread use in protein purification processes. However, the issue of fouling on the membrane surface frequently hampers the performance of PVDF membranes. The present study aims to enhance PVDF membranes' selectivity and antifouling properties through chitosan modification, thereby optimizing protein filtration. PVDF and PVDF/Chitosan membranes were fabricated using the phase inversion technique, followed by a comprehensive characterization of their surface properties, thermal attributes, and performance in bovine serum albumin (BSA) protein filtration. The collected data revealed notable increases in membrane hydrophilicity, porosity, and pure water flux due to the incorporation of chitosan. The membrane protein rejection capabilities were significantly enhanced to levels exceeding 90% with the introduction of 0.5% chitosan. Moreover, as the chitosan concentration increased, the membrane exhibited superior antifouling characteristics, with the 0.5% chitosan concentration yielding the highest Flux Recovery Ratio (FRR) value of 85.35%. Considering the significant improvement selectivity and antifouling properties in the combined system, the chitosan-modified PVDF membrane holds substantial promise in protein purification applications.